Princípio feminino gestador: uma nova abordagem na gestão - Motta, Fátima Therezinha (2009)
In this doctoral dissertation, it is defended the importance of recognizing the female principle as mother-principle , as origin, developing a new consciousness, grounded on the book Visão gestadora: a visão em teia (2008), written by Ramy Arany. I adopt, then, in this research work, as reference, the thesis that a progeny female principle is the origin capable of enabling a new model to administer, generate, being forward of companies and/or organizations of different sizes and sectors. However, it is not intended here to propose a replacement of a male model by another one conditioned to the female principle, nor rendering both principles (male and female) as one. Because of my 25 years of work in managerial capability programs, some inquiries related to the kind of management and its consequence on people have disturbed me quite often. On the other hand, at the same time my professional life went on, personal inquiries arose in me on the way I related to people and the way I let myself go on long and permanent bounds. I realized a duality between my personal life and professional one, what stimulated me to look for a path that led me to a clearer consciousness in myself, understood as something more sacred and essential. After several efforts, I came across Instituto KVT, founded by Ramy Arany and Ramy Shanaytá, who since 1995 have worked in the development of consciousness grounded in observation of natural laws. In this institute, research and intense living actions are carried out on evolution on consciousness of being and his/her evolutive stages. Therefore, I was able to take knowledge from female in developing the progeny consciousness, what certainly altered my values, beliefs, behaviors and I started to observe the applicability of all what I have learned there to my questionings regarding management. Thus, along with books, articles and essays selection, the development of this doctoral dissertation has been carried out on a set of interviews with Ramy Arany and a survey with enterprises managers, differing in their performance in sectors of activities and sizes, what led me to an effective recognition of progeny female principle as a new kind of management that might assist managers interested in developing harmonic relations in sustainable organizations